2020
DOI: 10.1177/1069072720935151
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Chinese Five-Factor Short Form of the Career Adapt-Abilities Scale

Abstract: The Career Adapt-Abilities Scale (CAAS) is a widely used measure to assess career adaptability. The initial design covered four areas — concern, control, curiosity, and confidence. Recent research validated a 12-item version of the scale (CAAS-SF) and a five-factor version that includes the additional factor of cooperation (CAAS-5). The study reported here developed and validated a brief 15-item Chinese version of Career Adapt-Abilities Scale (CAAS-5-SF) to include five factors. Based on data obtained in Macao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
(81 reference statements)
3
18
2
Order By: Relevance
“…One study also noted that males reported higher levels of curiosity and confidence (Yu et al, 2019). However, this finding is opposed with a previous study which showed that females were higher in the level of Concern and Confidence dimensions (Duarte et al, Hou et al, 2012;Sou et al, 2020) thus further explorations of this issue is deemed warranted.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…One study also noted that males reported higher levels of curiosity and confidence (Yu et al, 2019). However, this finding is opposed with a previous study which showed that females were higher in the level of Concern and Confidence dimensions (Duarte et al, Hou et al, 2012;Sou et al, 2020) thus further explorations of this issue is deemed warranted.…”
Section: Discussioncontrasting
confidence: 83%
“…With regards to difference in gender, research recounted varieties of mix and match findings. In this study, it was revealed that male students have higher levels of Control dimension than their counterparts (Hou et al, 2012;Sou et al, 2020;Leung et al, 2021) which shows that males are able to make own decision, take responsibility for own actions and depend on oneself. These characteristics show sense of maturity in male students, contradicting with previous studies (Abdinoor, 2020;Zahra & Malik, 2018).…”
Section: Discussionmentioning
confidence: 69%
“…Career adaptability was measured using Career Adapt‐Abilities Scale–Short Form (CAAS‐SF), which had previously been validated with a sample of college graduates in Macao (Sou et al., 2021). The scale contains four dimensions of concern, control, curiosity, and confidence, each with three items.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, social capital is an important resource for individuals during their job loss and job search process (Fugate et al., 2004). Among university graduates who are transitioning from school to work, those with more social capital achieve better subjective career success (Sou et al., 2021).…”
Section: Five‐factor Career Adaptability As a Mediator Between Social...mentioning
confidence: 99%
See 1 more Smart Citation